Genes Involved in Biofilm Matrix Formation of the Food Spoiler Pseudomonas fluorescens PF07 - Guo, Miao; Tan, Siqi; Zhu, Junli; Sun, Aihua; Du, Peng; Liu, Xiaoxiang (Frontiers in Microbiology, 2022)
The extracellular matrix is essential for the biofilm formation of food spoilers. Pseudomonas fluorescens PF07 is a previous isolate from spoiled marine fish; however, the genes involved in the extracellular matrix formation of PF07 biofilms remain poorly defined. In this study, PF07 formed a wrinkled macrocolony biofilm through the high production of extracellular matrix. The genes involved in biofilm matrix formation and regulation were screened and identified by RNA-seq-dependent transcriptomic analysis and gene knock-out analysis. The macrocolony biofilms of PF07 grown for 5 days (PF07_5d) were compared with those grown for 1 day (PF07_1d). A total of 1,403 genes were significantly differentially expressed during biofilm formation. These mainly include the genes related to biofilm matrix proteins, polysaccharides, rhamnolipids, secretion system, biofilm regulation, and metabolism. Among them, functional amyloid genes fapABCDE were highly upregulated in the mature biofilm, and the operon fapA-E had a -24/-12 promoter dependent on the sigma factor RpoN. Moreover, the RNA-seq analyses of the rpoN mutant, compared with PF07, revealed 159 genes were differentially expressed in the macrocolony biofilms, and fapA-E genes were positively regulated by RpoN. In addition, the deletion mutants of fapC, rpoN, and brfA (a novel gene coding for an RpoN-dependent transcriptional regulator) were defective in forming mature macrocolony biofilms, solid surface-associated biofilms, and pellicles, and they showed significantly reduced biofilm matrices. The fap genes were significantly downregulated in ΔbrfA, as in ΔrpoN. These findings suggest that the functional amyloid Fap is the main component of PF07 biofilm matrices, and RpoN may directly regulate the transcription of fap genes, in conjunction with BrfA. These genes may serve as potential molecular targets for screening new anti-biofilm agents or for biofilm detection in food environments.